A study on the characteristics and influencing factors of public sports service demand among the population of rural older adults in China - Zhang, Hai-pei; He, Cong-hui; Lu, Wen-yun (Frontiers in Public Health, 2025)
BackgroundWith the continuous deepening of China’s aging population, the high prevalence of chronic diseases, high disability rate and significant medical expenses among older adults have brought huge burdens to individuals, families and the entire social development. Compared with urban areas, the aging population in rural areas is severe and the population’s health status is worse. Therefore, how to scientifically address the issue of population aging in rural areas and minimize the negative effects of aging has become a focus of common concern in all sectors of society. As an important non-medical health intervention, exercise has been proven effective by scientific research and is also a common experience of developed countries in actively responding to the issue of population aging. However, the traditional one-way government supply model of rural public products has led to inefficient or ineffective supply of public sports services for a long time, making it difficult to meet the growing personalized needs of rural older adults. Therefore, a comprehensive understanding of the actual demands of rural older adults for public sports services, clarifying their demand types, structural characteristics and influencing factors, is the prerequisite for achieving an effective supply of public sports services for rural older adults and promoting their regular participation in sports.MethodsTo comprehensively understand the demand situation for public sports services for rural older adults, a sociological survey was conducted on the demand characteristics, influencing factors and satisfaction of public sports services for rural older adults aged 50 and above living in townships, corresponding towns and villages in the eastern, central and western regions of China. The research methods included a literature review, questionnaire survey, interview survey and statistical analysis.ResultsRural older adults have the most urgent demand for establishing sports fitness organizations, improving sports exercise guidance services and strengthening the construction of elderly sports systems; the demand for public sports services among rural older adults is influenced by multiple factors such as demographic characteristics, health status, individual lifestyle and sports exercise cognition level; the overall utilization rate of public sports services for rural older adults is low, and their satisfaction is at a medium level.ConclusionTo meet the public sports service demands of rural older adults, in the future, it is still necessary to enhance the demand subject consciousness of rural older adults, clarify the subjective demand picture of rural older adults, and improve the quality of public sports services for rural older adults.